Stories not written : Italo Calvino’s the castle of crossed destinies. - Cheong, Sylvia Chia Hwee. (2011)
The Castle of Crossed Destinies has received scant attention as compared to Calvino’s other novels, and many critics have seen Calvino’s game of storytelling with tarot cards negatively. The author’s apparent abandonment of the combinatory game is often interpreted by critics as revealing through participating in a “wasted exercise” (Markey, “Paradox of Choice” 68) a writer’s dilemma with choices. However, while Calvino reveals that it is impossible to arrive at all the possible stories the tarot cards are able to generate within the space of the novel, The Castle of Crossed Destinies brings into play and juxtaposes different narrative mediums to generate various realised and unrealised possibilities of narration, thus inviting the reader to read within the spaces created in the tension and interaction of these mediums. These narrative mediums consist of the written word and images and it is the spaces between these different mediums that reveal the combinatory game as a success rather than a failure. Through effecting a sense of lightness both within and between these storytelling mediums, Calvino makes such spaces ideal for capturing an infinite number of stories within The Castle of Crossed Destinies. In this essay, I shall explore how Calvino sets up the site of storytelling and draws our attention to the interaction between the written word and the image, how he engages readers to read the spaces created out of the interaction of the two mediums, and how as Calvino dismantles the game he sets up, he reveals that his apparent giving up of the tarot game need not necessarily mean that the combinatory game ends in futility.